Ownership and the Internationalization of Small Firms - GEORGE, Gerard (Institutional Knowledge at Singapore Management University, 2005)
Small and medium-sized enterprises (SMEs) play an important role in international markets. This study argues that the ownership structures of SMEs influence their proclivity to take risks and expand the scale and scope of their internationalization efforts. Data from 889 Swedish SMEs reveal that internal owners (CEOs and other senior executives) tend to be risk averse and have a lower proclivity to increase scale and scope of internationalization than external owners (venture capitalists and institutional investors). The results provide interesting insights into the behavioral change of executives regarding the scale and scope of internationalization in the presence of external ownership.